PEREMPUAN BUTA TANPA IBU JARI DAN CINDERELLA AND THE GLASS SLIPPER: KAJIAN DEKONSTRUKTIF - Syam, Essy (Jurnal Ilmu Budaya, 2010)
This writing deals with a study on showing how a short story entitles Perempuan Buta tanpa Ibu Jari deconstructs the most well-known clasicalls foklore Cinderella and The Glass Slipper